Problematika Poligami dalam Lintas Sejarah dan Agama - Elva Imeldatur Rohmah (Fakultas Syariah dan Hukum UIN Sunan Ampel Surabaya, 2022)
This paper aims to determine the phenomenon and problems of polygamy throughout history and the views of several religions on polygamy. This article was written using a descriptive-analytical method. The result is that almost all nations in the world, from time immemorial, have been familiar with polygamy. For example, since time immemorial, polygamy has been known by Hindus, Israelis, Persians, Roman Arabs, Babylonians, Tunisians, and others. Polygamy also extends to the Hebrews and Sicilians, who later gave birth to most of the Russians, Lithuanians, Poles, Czechoslovakia, and Yugoslavia, as well as part of the population of Germany, Switzerland, the Netherlands, Denmark, Sweden, Norway, and England. Polygamy exists in every human civilization. Islam, Christianity, Hinduism, Buddhism, and Judaism do allow polygamy, although, in essence, the principle of marriage taught in these religions is monogamy. Meanwhile, modern Church Law forbids its followers from polygamy. The Qobty Orthodox Church, the Roman Orthodox Church, and the Syriac Orthodox Church do not allow a husband or wife to have a second marriage as long as the first marriage is still ongoing or has not been cancelled. So, a marriage that is recognized as legal is the marriage of a man to a woman, and polygamy is not allowed. Abstrak: Tulisan ini bertujuan untuk mengetahui fenomena dan problematikan poligami sepanjang sejarah dan pandangan beberapa agama tentang poligami. Artikel ini ditulis dengan menggunakan metode deskriptif analitis. Hasilnya adalah hampir seluruh bangsa di dunia, sejak zaman dahulu kala tidak asing dengan poligami. Misalnya, sejak dahulu kala poligami telah dikenal oleh orang-orang Hindu, bangsa Israel, Persia, Arab Romawi, Babilonia, Tunisia, dan lain-lain. Poligami juga meluas pada bangsa Ibrani dan Sicilia yang kemudian melahirkan sebagian besar bangsa Rusia, Lithuania, Polandia, Cekoslowakia, dan Yugoslavia, serta sebagian penduduk Jerman, Swiss, Belanda, Denmark, Swedia, Norwegia, dan Inggris. Poligami ada dalam setiap peradaban manusia. Dalam agama Islam, Nasrani, Hindu, Budha, maupun Yahudi memang memperbolehkan adanya poligami, meskipun pada hakikatnya asas pernikahan yang diajarkan dalam agama-agama tersebut adalah monogami. Sedangkan Undang-undang Gereja modern mengharamkan pengikutnya berpoligami. Gereja Qobty Ortodoks, Gereja Roma Ortodoks, dan Gereja Suryani Ortodoks tidak membolehkan seorang suami atau istri melakukan pernikahan kedua, selama pernikahan pertama masih berlangsung atau belum dibatalkan. Jadi, pernikahan yang diakui sah adalah pernikahan seorang laki-laki dengan seorang perempuan, dan poligami tidak diperbolehkan.